Interstitial Lung Disease in Primary Sjögren’s Syndrome: Risk factors for occurrence and radiographic progression: Interstitial lung disease associated with primary Sjögren's syndrome - Konak, Hatice Ecem; Atalar, Ebru; Hezer, Habibe; Koçak Ulucaköy, Rezan; Kayacan Erdoğan, Esra; Babaoğlu, Hakan; Armağan, Berkan; Orhan, Kevser; Doğan, İsmail; Maraş, Yüksel; Omma, Ahmet; Karalezli, Ayşegül; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Objectives: The aim of this study is to investigate the characteristics of Primary Sjögren's syndrome (pSS)- interstitial lung disease (ILD) patients and compare them to those of pSS patients without ILD in the tertiary pSS-ILD cohort to evaluate potential risk factors for ILD occurrence and disease progression. Methods: Patients followed up who met the 2016 American College of Rheumatology-European League Against Rheumatism classification criteria for pSS were retrospectively analyzed. The patients were grouped as those with ILD and those without ILD according to medical records. High-resolution computed tomography (HRCT)/ thorax CT (TCT) results of all ILD patients were evaluated. Data on demographics, comorbidities, clinical characteristics and laboratory findings were collected. Results: A total of 378 pSS patients, including 60 with ILD and 318 without ILD were detected to have at least one obtainable HRCT/TCT and were included in the study. In the cohort of pSS patients with at least one HRCT or TCT, the frequency of ILD was 15.8%. In the ILD group, the most common HRCT pattern was NSIP, and the most common findings were ground glass opacities, traction bronchiectasis, and honeycombing. Logistic regression analysis showed that male gender (OR:2.90), being diagnosed with pSS over the age of 50(OR:4,24), smoking history (OR:2.38), elevated LDH(OR:3.27), elevated ESR(OR:2.51) and lymphopenia (OR:5.12) were related with development of ILD while being diagnosed with ILD after the age of 60 (OR:8.5) was related with radiographic progression. Conclusion: The study results provided a large spectrum view for pSS-ILD and pointed out several risk factors for ILD occurrence and radiographic progression.